Analisis Perbedaan Disclosure Kinerja Corporate Social Responsibility Sebelum Dan Pasca Era New Normal Di Perusahaan Perbankan - Supaidatul Jannah; Justita Dura (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2022)
The Covid-19 pandemi has had an impact on all sectors, especially the banking sector. Therefore, researchers analyzed the banking sector on the disclosure of corporate social responsibility economic performance, environmental performance and social performance before and after the new normal era. The number of samples used were 90 companies in 2019-2020 based on the nonprobability sampling method with purposive sampling technique. The analytical technique used is a different test. The type of data used in this study is quantitative and the data sources used are included in secondary data. The results show that [1] there are differences in disclosure of economic performance before and after the new normal era, [2] there are no differences in disclosure of environmental performance before and after the new normal era, [3] there are differences in disclosure of social performance before and after the new normal era